2004
DOI: 10.1080/09583150410001682296
|View full text |Cite
|
Sign up to set email alerts
|

Selected cultural and environmental parameters influence disease severity of dandelion caused by the potential bioherbicidal fungi,Phoma herbarumandPhoma exigua

Abstract: Selected cultural and environmental variables were investigated for their influence on the efficacy of Phoma herbarum and Phoma exigua to cause disease on dandelion (Taraxacum officinale) under growth room conditions. In both species, mycelial fragments caused significantly greater disease severity on dandelion than spore suspensions. Mycelial age was not an important factor in disease severity caused by P. herbarum, with all cultures causing high disease ratings. However, younger cultures of P. exigua caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Our results show that Phoma mycelia causes more disease than conidia and confirms reports that Phoma mycelia are more infective than conidia (Neumann and Boland 2002;Stewart-Wade and Boland 2004). Another important requirement for establishment of disease is inoculum concentration.…”
Section: Effect Of P Argillacea On Nontarget Hostssupporting
confidence: 93%
See 2 more Smart Citations
“…Our results show that Phoma mycelia causes more disease than conidia and confirms reports that Phoma mycelia are more infective than conidia (Neumann and Boland 2002;Stewart-Wade and Boland 2004). Another important requirement for establishment of disease is inoculum concentration.…”
Section: Effect Of P Argillacea On Nontarget Hostssupporting
confidence: 93%
“…Another important requirement for establishment of disease is inoculum concentration. Increasing the inoculum concentration often confers greater initial disease severity as reported on other plant-pathogen systems, such as the dandelion-Phoma system (Neumann and Boland 2002;Stewart-Wade and Boland 2004). Our study showed that various dilutions of P. argillacea mycelia, when provided with sufficient leaf wetness period, causes high disease severity (>70%) and can be effectively used at low concentrations (0.5% (v/v) or 3.5 × 10 2 CFU/mL).…”
Section: Effect Of P Argillacea On Nontarget Hostsmentioning
confidence: 59%
See 1 more Smart Citation
“…For example, mycelial suspensions of P. herbarum incited significantly more disease severity than conidia on dandelion (Taraxacum officinale Weber) [48]. Similarly, mycelial fragments of P. exigua and P. herbarum incited significantly more disease severity of T. officinale than fungal conidia [49]. Zhao and Shamoun [36] found that culture growth media and age of mycelial cultures could affect the disease severity of P. exigua on the perennial evergreen weedy shrub, salal (Gaultheria shallon Pursh).…”
Section: Disease Progression Of P Commelinicola On C Diffusa Under mentioning
confidence: 99%
“…was isolated from leaf lesions on dandelion in southern Ontario (Neumann Brebaum & Boland 1999). The potential of P. herbarum as a bioherbicide for dandelion was studied in controlled environments and optimal leaf wetness duration for high disease severity was 16 Á/24 h continuous or 2)/12 h discontinuous (i.e., interrupted by 12 h) (Neumann Brebaum 1998;Stewart-Wade & Boland 2004). The addition of adjuvants increased disease severity of dandelion caused by P. herbarum in both controlled and field environments, but there was variation in disease severity between field seasons .…”
mentioning
confidence: 99%